Implementation of Solar Cell and Photocell-Based Street Lighting in Gaprang Village, Blitar - Reza Sarwo Widagdo; Ardianik; Puji Slamet; Aris Heri Andriawan; Imam Suri Tauladan; Balok Hariadi (Pelita: Jurnal Pengabdian kepada Masyarakat, 2025)
The increasing demand for sustainable energy sources has encouraged the application of renewable technologies in rural infrastructure, particularly in public lighting systems. This study focuses on the implementation of solar cell and photocell-based street lighting in Gaprang Village, Blitar Regency, as a solution to reduce dependency on conventional electricity and to enhance energy efficiency. The system utilizes photovoltaic modules as the primary energy source to convert solar radiation into electrical power, which is stored in batteries and subsequently used to supply street lamps during nighttime. In addition, the integration of photocell sensors enables automatic control of the lighting system by detecting environmental illumination levels, ensuring that the lamps operate only when required. The design and installation process involved site surveying, load estimation, solar panel configuration, and the application of photocell-based automation. The results demonstrated that the system provided reliable illumination for rural roads, significantly lowering operational costs and minimizing environmental impact compared to traditional grid-powered lighting. Furthermore, the use of photocells improved energy management by preventing unnecessary power consumption during daylight. The activity will take place in August 2025, with a focus on installation in Gaprang Village. The results of the activity include community understanding of the benefits and maintenance of street lights, as well as the implementation of solar cell-based technology. The conclusion states that this project can provide a positive and sustainable impact, empowering communities and creating efficient infrastructure that aligns with renewable energy initiatives.